How Do Vocational Students Perceive the Use of Telegram for their Online Reading Comprehension? - Suci, Dewi Nur; Basthomi, Yazid; Cahyono, Bambang Yudi; Anugerahwati, Mirjam; Masuara, Faradila; Anggraini, Merliyani Putri (HERMES - Journal of Language and Communication in Business, 2022)
The advancement of technology encourages English teachers to use online platforms and applications in their English teaching and learning process. There are many apps that can be employed, one of which is Telegram. This study investigates how students perceive the use of Telegram on their reading comprehension and the correlation between the perception and their reading comprehension. For this purpose, 104 students from an Indonesian vocational school from various majors completed an online questionnaire about the use of Telegram for learning English. Besides, a reading test was used to measure the students’ reading comprehension. The results portray that the students across departments positively perceived the use of Telegram on their reading comprehension. Furthermore, this study reveals a weak correlation between how the students perceive the use of Telegram and their reading comprehension. It is signified by the correlation between the two variables of interest, .364, which is significant at the .000 level. It indicates that the student’s perception and reading comprehension for this set of data were significant but had a weak relationship. This may be caused by the reading strategies instructions as the teacher did not provide guidance before the treatment. It yields the pedagogical implication that teachers should train their students to use reading strategies effectively for their online reading comprehension.